2021
DOI: 10.1371/journal.pone.0258179
|View full text |Cite
|
Sign up to set email alerts
|

Association of prenatal sex steroid exposure estimated by the digit ratio (2D:4D) with birth weight, BMI and muscle strength in 6- to 13-year-old Polish children

Abstract: Objectives The aim of this paper was to provide evidence for the impact of prenatal sex steroid exposure on prenatal and postnatal body size parameters, and muscle strength in children. Methods The following anthropometric data were studied in a group of 1148 children (536 boys and 612 girls) aged 6–13 years: the 2D:4D digit ratio, birth weight and length, and birth head and chest circumference. Postnatal parameters (6–13 years) included body weight and height, BMI, waist and hip circumference, WHR, as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Many other authors have also demonstrated that 2D:4D not only of the right hand, but also of the left hand, positively correlates with body mass index (BMI) in adults of both sexes 32 , 33 . Other research revealed a positive relationship between BMI and 2D:4D, but only for the right hand 34 , 35 . On the other hand, Fink et al found that BMI in men (but not in women) is positively related to the digit ratio, but it remains significant only for the left hand 36 .…”
Section: Discussionmentioning
confidence: 87%
“…Many other authors have also demonstrated that 2D:4D not only of the right hand, but also of the left hand, positively correlates with body mass index (BMI) in adults of both sexes 32 , 33 . Other research revealed a positive relationship between BMI and 2D:4D, but only for the right hand 34 , 35 . On the other hand, Fink et al found that BMI in men (but not in women) is positively related to the digit ratio, but it remains significant only for the left hand 36 .…”
Section: Discussionmentioning
confidence: 87%
“…However, while the 2D:4D ratio is often seen as a surrogate marker for intrauterine testosterone exposure, the observation of a missing association of testosterone levels in amniotic fluid with the 2D:4D ratio only recently failed to confirm this idea [27], a finding questioning the validity of this measure. In addition, it has been shown that the 2D:4D length ratio varies, e.g., with maternal smoking [31] or birth weight [17], which are both not per se associated with intrauterine testosterone exposure.…”
Section: Discussionmentioning
confidence: 99%
“…In other studies on children, the relationship between 2D:4D ratio and cortisol, vitamin D level and body composition, and the relationship between 2D:4D ratio and fitness level were evaluated 23 , 24 . There are studies suggesting that prenatal sex steroid exposure may be a risk factor for migraine in adults and may be associated with birth weight, BMI and muscle strength in children 25 , 26 .…”
Section: Introductionmentioning
confidence: 99%